Analysis of Law Enforcement to Drugs Criminal Act in Military Environment (Case Study in Jurisdiction of Military Court II/09 Bandung) - Asep Suherdin; Maryanto Maryanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The problems of this study are: 1) How is enforcement against members of the military in drug abuse in the jurisdiction of the Military Court II/09 Bandung? 2) How constraints and efforts to overcome the constraints of law enforcement against members of the military in drug abuse in the jurisdiction of the Military Court II/09 Bandung?Method sociological approach juridical law and specification in this study were included descriptive analysis. Even the sources and types of data in this study are primary data obtained from interviews with field studies Military Court II/09 Bandung, and secondary data obtained from the study of literature. Data were analyzed qualitatively. The problems studied by the theory of law enforcement, criminal liability and progressive law.Results of the discussion concluded: Enforcement of the law against members of the military in drug abuse in the jurisdiction of the Military Court II/09 Bandung executed in accordance with the applicable regulations, because the urine test is done not in accordance with regulations and charges denied by the defendant who has the right of refusal. The obstacles are the lack military justice, the need for strengthening of the system of criminal law enforcement in the military justice ahead of independent both institutionally and functionally, free from interference by other institutions outside the judiciary as a logical consequence system of a democratic constitutional state, so it is necessary No reconstruction of the existing regulation of military justice. Next to the military justice system, particularly related to the investigation should be conducted by military police consisting of the Army, Navy and Air Force, independently.Keywords: Law Enforcement; Crime; Drugs; Military Environment.